codY and pdhA Expression Is Induced in Staphylococcus epidermidis Biofilm and Planktonic Populations With Higher Proportions of Viable but Non-Culturable Cells - Gaio, Vânia; Lopes, Nathalie; Cerca, Nuno; França, Angela (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus epidermidis biofilm cells can enter a physiological state known as viable but non-culturable (VBNC), where, despite being alive, they do not grow in conventional laboratory media. As such, the presence of VBNC cells impacts the diagnosis of S. epidermidis biofilm-associated infections. Previous transcriptomics analysis of S. epidermidis strain 9142 biofilms with higher proportions of VBNC cells suggested that the genes pdhA, codY and mazEF could be involved in the induction of the VBNC state. However, it was previously demonstrated that VBNC induction is strain-dependent. To properly assess the role of these genes in VBNC induction, the construction of mutant strains is necessary. Thus, herein, we assessed if VBNC cells could be induced in strain 1457, a strain amenable to genetic manipulation and if the previously identified genes were involved in the modulation of the VBNC state in this strain. Furthermore, we evaluated the formation of VBNC cells on planktonic cultures. Our results showed that despite being commonly associated with biofilms, the proportion of VBNC cells can be modulated in both biofilm and planktonic cultures and that the expression of codY and pdhA was upregulated under VBNC inducing conditions in both phenotypes. Overall, our study revealed that the formation of VBNC cells in S. epidermidis is independent of the mode of growth and that the genes codY and pdhA seem to be relevant for the regulation of this physiological condition.